Role of Print Media in Preserving Culture: With Special Reference to local publications of Birbhum District - Roy, Debjani; Sen, Prof. Sabujkoli; Chand Saha, Dr. Nimai (IJRDO - Journal of Social Science and Humanities Research, 2017)
Culture and media is inseparable because media is part of culture. Media represents the various cultural heritages, activity, as it is the mediator between culture and people. Media transmits the messages in its own and it cannot directly change the attitude of the people and the culture. Culture promotion and preservation is an important challenge to media to outreach. Media creates awareness of communication. The multiple cultures are represented in cultural communication. The highlights of different newspapers are given from the district and then the complete analysis of data is done based on the data collected from different sources and ultimate conclusion and suggestion is evaluated based on the interpretation. The final conclusion is drawn.